Democratic Leadership of School Administrators Under the Samut Prakan Primary Educational Service Area Region 1 - Kajadjon, Somruedee; Silanookit, Chonmanee (Journal of Humanities and Social Sciences Loei Rajabhat University, 2023)
The objectives of this research were to study the democratic leadership of school administrators under the Samut Prakan Primary Educational Service Area Office, Region 1, and to compare the democratic leadership of school administrators under the Samut Prakan Primary Educational Service Area Office, Region 1. The sample consisted of 295 teachers selected through simple random sampling. The tool used to collect data was a questionnaire with a 5-level estimation scale that had a concordance index between 0.80 - 1.00. Data were collected with a reliability efficiency index of 0.937, and analyzed using frequency, percentage, mean, and standard deviation. The research found that: (1) The democratic leadership of school administrators under the Samut Prakan Primary Educational Service Area Office, Region 1, overall and by aspect, was at a high level both overall and in individual aspects. (2) Teachers with different educational backgrounds and work experiences had opinions on democratic leadership of school administrators under the Samut Prakan Primary Educational Service Area Office, Region 1 overall, there was no differences. (3) Teachers with different school sizes had opinions on democratic leadership of school administrators under the Samut Prakan Primary Educational Service Area Office, Region 1 overall, there was no differences. But there was a significant difference in the Empowering aspect.